The Pathologic Findings of Skin, Lymph Node, Liver, and Bone Marrow in Patients With Adult-Onset Still Disease. Issue 17 (May 2015) - Kim, Hyoun-Ah; Kwon, Jee Eun; Yim, Hyunee; Suh, Chang-Hee; Jung, Ju-Yang; Han, Jae Ho; Cheng., Xiwen
<x xml:space="preserve">Abstract</x> Abstract Adult-onset Still disease (AOSD) is characterized by fever, skin rash, and lymphadenopathy with leukocytosis and anemia as common laboratory findings. We investigated the characteristic pathologic findings of skin, lymph node, liver, and bone marrow to assist in proper diagnosis of AOSD. Forty AOSD patients were included in the study. The skin (26 patients), lymph node (8 patients), liver (8 patients), or bone marrow biopsies (22 patients) between 1998 and 2013 were retrospectively analyzed. AOSD patients were diagnosed according to the Yamaguchi criteria after excluding common infections, hematological and autoimmune diseases. Immunohistochemistry, immunofluorescence, and Epstein–Barr virus–encoded RNA (EBER) in situ hybridization were performed. Most skin biopsies revealed mild lymphocytic or histiocytic infiltration in the upper dermis. Nuclear debris was frequently found in the dermis in 14 cases (53.8%). More than half of the cases (n = 14, 53.8%) showed interstitial mucin deposition. Some cases showed interface dermatitis with keratinocyte necrosis or basal vacuolization (n = 10; 38.5%). The lymph node biopsies showed a paracortical or diffuse hyperplasia pattern with immunoblastic and vascular proliferation. The liver biopsies showed sparse portal and sinusoidal inflammatory cell infiltration. All cases showed various degrees of Kupffer cell hyperplasia. The cellularity of bone marrow varied from 20% to 80%. Myeloid cell hyperplasia was found in 14 out of the 22 cases (63.6%). On immunohistochemistry, the number of CD8-positive lymphocytes was greater than that of CD4-positive lymphocytes in the skin, liver, and bone marrow, but the number of CD4-positive lymphocytes was greater than that of CD8-positive lymphocytes in the lymph nodes. The relatively specific findings with respect to the cutaneous manifestation of AOSD were mild inflammatory cell infiltration in the upper dermis, basal vacuolization, keratinocyte necrosis, presence of karyorrhexis, and mucin in the dermis. In all cases, pathologic findings in the lymph nodes included paracortical hyperplasia with vascular and immunoblastic proliferation. Skin and lymph node pathology in addition to clinical findings can aid in the diagnosis of AOSD.